2019
DOI: 10.1021/acs.chemrev.9b00460
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Polyphosphates As Storage for and Generator of Metabolic Energy in the Extracellular Matrix

Abstract: Inorganic polyphosphates (polyP) consist of linear chains of orthophosphate residues, linked by high-energy phosphoanhydride bonds. They are evolutionarily old biopolymers that are present from bacteria to man. No other molecule concentrates as much (bio)chemically usable energy as polyP. However, the function and metabolism of this long-neglected polymer are scarcely known, especially in higher eukaryotes. In recent years, interest in polyP experienced a renaissance, beginning with the discovery of polyP as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(161 citation statements)
references
References 363 publications
3
158
0
Order By: Relevance
“…Several biological functions have been identified for cellular polyP including buffering capacities for pH homeostasis, DNA damage repair, cell cycle, motility, and biofilm formation [49][50][51]. Studies in other bacteria showed that polyP was rapidly accumulated by PPK under environmental stresses including acidic conditions [52][53][54]. Our transcriptomic data indicated that the expression of ppk in wild-type ZM4 was upregulated under acidic pH compared with neutral pH (Table S2), which is consistent with above reported conclusion.…”
Section: Association Of Genes With Common Changes In Mutants With Enhsupporting
confidence: 90%
“…Several biological functions have been identified for cellular polyP including buffering capacities for pH homeostasis, DNA damage repair, cell cycle, motility, and biofilm formation [49][50][51]. Studies in other bacteria showed that polyP was rapidly accumulated by PPK under environmental stresses including acidic conditions [52][53][54]. Our transcriptomic data indicated that the expression of ppk in wild-type ZM4 was upregulated under acidic pH compared with neutral pH (Table S2), which is consistent with above reported conclusion.…”
Section: Association Of Genes With Common Changes In Mutants With Enhsupporting
confidence: 90%
“…Several biological functions have been identi ed for cellular polyP including buffering capacities for pH homeostasis, DNA damage repair, cell cycle, motility, and bio lm formation [48][49][50]. Studies in other bacteria showed that polyP was rapidly accumulated by PPK under environmental stresses including acidic conditions [51][52][53]. Our transcriptomic data indicated that the expression of ppk in wild-type ZM4 and mutant strains was upregulated at pH 3.8 compared with pH 6.2 (Table S2), which is consistent with the conclusion reported above.…”
Section: Resultsmentioning
confidence: 99%
“…It has been pointed out that polyP has a high degree of rotational flexibility, paralleled with various conformations, like staggered or eclipsed, which depend on the arrangement of the tetrahedral PO 4 units. 13,43 Modification of Arg with 1,2-cyclohexanedione…”
Section: Alignment Of Polyp On the Rbdmentioning
confidence: 99%
“…12 Now during the search for compounds acting as potential inhibitors of SARS-CoV-2 infection that might gain therapeutic impact, we studied the effects of the natural polymers of polyP (reviewed in: ref. 13) andin comparisonof heparin on the binding of the virus to the target cells. A model system was applied for these studies, a binding assay, in which the cellular receptor for SARS-CoV-2, the recombinant angiotensin-converting enzyme 2 (ACE2), 14 was attached to the well plate and the labeled receptor-binding domain (RBD) of the SARS-CoV-2 spike (S)-protein was used as a detector molecule.…”
Section: Introductionmentioning
confidence: 99%